Fred Ross smiling. - Sahl, Ted (photographer):::Creator::::::::::::
Written on recto: Fred Ross community sevice organization hired Chavez to join org to benefit farm workers in Oxnard, CA. UFW anniv. 20th anniv. Sacred Heart Church S.J.